CRITICAL DISCOURSE: APPLYING NORMAN FAIRCLOUGH THEORY IN RECEP TAYYIP ERDOĞAN’S BALCONY SPEECH - Rika Wahyuni Tambunan; Muhizar Muchtar; Putri Agustian; Agus Salim; Laili Aisyah; Budi Awan Marpaung; Muhammad Muslim Nasution (Universitas Negeri Padang, 2018)
This research aimed to apply Norman Fairclough theory in the Recep Tayyip Erdogan’s balcony speech in front of the party's headquarters, Arkan, Turkey. This research used Norman Fairclough theory of the textual analysis, analysis of the practice of discourse, and analysis of sociocultural. The method used in this study is a qualitative research method to approach critical discourse analysis. This study used observation techniques. The results obtained are as follows: (1) The textual analysis in his official greeting speech of Erdogan consist of three parts: the text structure, grammar and coherence. (2) Analysis of the practice of three stages: namely the process of earning a discourse, process deployment, and the use of discourse. (3) Analysis of sociocultural practices in his official speech of Erdogan consist of three levels, namely the level of: situational, institutional, and social.